The Effect of Adding Neoadjuvant Chemotherapy to Concurrent Chemoradiotherapy in Patients with Locoregionally Advanced Nasopharyngeal Carcinoma and Undetectable Pretreatment Epstein-Barr Virus DNA - Jin, Ya-Nan (Transl Oncol, 2017)
PURPOSE: To assess the effect of adding neoadjuvant chemotherapy (NACT) to concurrent chemoradiotherapy (CCRT) in patients with locoregionally advanced nasopharyngeal carcinoma (NPC) and undetectable pretreatment Epstein-Barr virus (pEBV) DNA. MATERIALS AND METHODS: We enrolled 639 NPC patients with stage II to IVB and undetectable pEBV DNA to receive CCRT with or without NACT. Radiotherapy was 2.0 to 2.27 Gy per fraction with five daily fractions per week for 6 to 7 weeks to the primary tumor and 62 to 70 Gy to the involved neck area. NACT was cisplatin (80-100 mg/m(2) day 1) and 5-fluorouracil (800-1000 mg/m(2), 120-hour continuous intravenous infusion) every 3 weeks for two or three cycles. CCRT was cisplatin (80-100 mg/m(2) day 1) every 3 weeks for three cycles. RESULTS: For all patients, the 5-year overall survival (OS), locoregional relapse-free survival (LRFS), distant metastasis-free survival (DMFS), and progression-free survival (PFS) rates were 91.9%, 92.2%, 95.0%, and 86.4%, respectively. There was no significant difference in OS (5-year OS 90.8% [NACT + CCRT group] vs 92.7% [CCRT alone]; hazard ratio [HR] 1.24; P = .486), LRFS (HR 1.13, 95% confidence interval [CI] 0.59-2.14, P = .715), DMFS (HR 0.78, 95% CI 0.34-1.78, P = .554), or PFS (HR 1.21, 95% CI 0.75-1.95, P = .472). CONCLUSION: CCRT with or without NACT produced a good treatment outcome in patients with locoregionally advanced NPC and undetectable pEBV DNA, but NACT before CCRT did not significantly improve survival rates.